Trap Sequence: Case Report - Sümeyra Nergiz; Selda Demircan Sezer; Sündüz Özlem Altınkaya; Mert Küçük; Alparslan Ünsal; Ali Rıza Odabaşı; Hasan Yüksel (Medical Network, 2016)
TRAP (Twin Reversed Arterial Perfusion) sequence is a rare syndrome seen in monochorionic twin pregnancies. It occurs in 1% of monochorionic twin pregnancies. It is characterized with a recipient fetus exhibiting lethal anomalies including acardia and a pump fetus supplying blood by vascular anastomosis in the placenta. Pump twin is structurally normal but heart failure may develop with cardiomegaly, pericardial and pleural effusion, ascites and polyhydramnios also seen during pregnancy. This anomaly has high mortality for pump twin and is always lethal for recipient. Here, a TRAP sequence case diagnosed at 14 weeks of gestation in antenatal period and followed up spontaneously until labor, with the demand of the family is presented.